PLANEACIÓN FINANCIERA PARA LA CLÍNICA CEVASCOP S.A, (MEDILAB) DE LA CIUDAD DE LOJA PERÍODO, 2016 - 2018 - Romero Montaño, Blanca Cecilia (2016)
This paper called Financial Planning Research for Cevascop Company S.A. (Clinical Medilab) of the city of Loja, period 2016-2018 "aims to set goals, choose operational and financial strategies that help predict outcomes to meet financial activities proposed by the Directors of the Clinic. To carry out this work all the necessary information was compiled through interviews and survey of the Manageress and bookkeeper of society, in order to detect the problem by setting their causes, effects and possible solutions. He worked with assistants who served Income and expenses for carrying out the programs of cash inflows and outflows, the same that underlie the projected cash budget. Similarly as was provided for in one of the specific objectives of the United Proforma them that are of great importance because through these an estimated revenues and expenses generated in the future society is presented it is presented.In this context it is concluded that financial planning CEVASCOP applied to the Company S.A., shows that once made a revenue forecast for the company profitability is observed; then we have the determination and analysis Budget Cash where the projected cash it can be used in operating activities and financing, being useful to the process of financial planning is shown as it is obtained results in a positive cash flow in the entity. Subsequently Proforma Financial Statements, consisting of the income statement which shows you revenue and expected costs and the Statement of Financial Position indicating the expected financial position is made; that is, assets, liabilities and equity for the period 2016-2018. Finally the conclusions and recommendations of all the research work were raised.